Word formation in Chronicle of Peru by Cieza de León - Cuba M., María del Carmen (2014)
In this paper is analyzes some morphological mechanisms in lexical construction embodied in the book "Chronicle of Peru, first Part" of Pedro Cieza de León. The aim is to report on a stage in the evolution of the lexicon of the Castilian brought by the Spaniards. Specifically, it is the formation or structure of certain words used by Spanish intellectuals in colonial times. The particular manner of forming words has to do with some derivatives and lexical morphemes used Cieza in this work, as one of the academic representatives of the time. Only described the form adding prefixes and suffixes and even the way that has the lexical morpheme as reference the Latin and the actual Spanish, especially in America.